Non-military challenges in the Black Sea - Bocai, Adina Elena (Technium Business and Management, 2023)
Ethnic groups or national minorities are far from being understood as stable and convergent units in the nation’s security efforts. This issue is backed by a substantial scientific record, treated differently in relation to the prevalence of certain political, economic, social and, above all, cultural factors. From an academic point of view, the record of ethnicity-security relations is not uniform and convergent either. Different schools of thought in the political science and security fields look at the issue from different angles. The present article aims to highlight a number of issues related to non-military challenges in the Wider Black Sea Region in the context of the war in Ukraine. We will further assess possible vulnerabilities in the Black Sea riparian states that may become a threat to national security.